The Contribution of Sufism in Building and Advancing Islamic Civilization in Indonesia: Kontribusi Tasawuf dalam Membangun dan Memajukan Peradaban Islam di Indonesia - mursalat mursalat (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2022)
Sufism is accused of being a 'virus' that hinders progress and causes the Muslim world to lag in the arena of modern civilization. Sufism teachings and doctrines are considered irrelevant to the spirit of the global era and modernism. Likewise, puritan Islamic groups regard Sufism as a heresy and misleading superstition, as we have seen recently with the emergence of radical-puritan/salafi-Salafi-Wahabic groups. Sufism and Civilization. The two fields seem to be separate. Sufism is often perceived as an individual inner world, an ascetic activity that is super closed close material world. While civilization is something that requires the manifestation of progress, both physical and non-physical. Can the two of them meet, how is the relationship between the two, negate or affirm, if the answer is positive and affirmative, we can trace the relationship between Sufism and civilization from the relationship between Islam and civilization. Judging from the type of research, this research is included in qualitative research. It is said to be qualitative because this research emphasizes more on presenting the existing data descriptively. The results of this study explain that the important role of Sufism is awaited again to restore the glory of Islamic civilization, especially in Southeast Asia, in the mamidative views of some Muslims towards Sufism. Sufism is actually the of Islam being able to enter from various fields iing health, peace, economics, social, politics and culture.  Keywords :  Islamic civilization, sufism, advanced civilization